Hadith #205 - Sahih al-Bukhari - Ja'far bin 'Amr bin Hryth جعفر بن عمرو بن حريث (Sahih al-Bukhari)
My father said, “I saw the Prophet (ﷺ) passing wet hands over his turban and Khuffs (socks made from thick fabric or leather).
Grade: Sahih